Penanaman Agama Islam dalam Pendidikan Informal - Yulianti, Asri; Hilma Ashyla, Fatika; Indah Pertiwi, Melani; Fajrussalam, Hisni (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
In the very first stages of formation and inculcation of educational knowledge that will bereceived by each individual, of course, it will start from within or from the closest are familyor the closest environment as the first education or informal education. Planting knowledge isnot only from one side, therefore religious education also needs to be educated from an earlyage through informal education. Islamic religious education which serves as one of thedriving factors in the formation of good education for the future. Therefore, the cultivation ofIslamic religious values in informal education certainly requires good provision andpreparation from all sides for the provision and application of it. In this study using theliterature study method and has references from journals that are accessed from GoogleScholar